Family Structure, Usual and Preferred Working Hours and Egalistarianism in Australia - Tseng, Y; Wooden, M; Drago, R (My University, 2004)
Data from a representative survey of adult Australians are analysed for usual and preferred working time across family types. We discover a time divide regardless of gender and family type: many short hours individuals desire longer hours of employment, while many long hours individuals prefer shorter hours. The latter group is larger such that the average employee desires fewer hours across family types, with the exception of lone mothers. For dual-earner couples with children, men average approximately 20 hours more per week than women, a difference that would only decline to 18 hours per week if preferred hours were realized. However, approximately one-fifth of these couples exhibited egalitarian or nearly equal working hours. Egalitarian couples averaged a combined 84 hours per week of employment, tended to share the care of children, were more likely to be non-Australian born, and included marked numbers of women holding degrees and in professional occupations.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Employment -- Hours; Families; Families and relationships; Labour market; Employment and unemployment; Families and relationships